Interlink between stress and periodontal disease - Reddy, S; Kaul, S; Prasad, M G S; Agnihotri, J; Amudha, D; Vinayak, R (Health Renaissance, 2012)
Stress is a term that is commonly used today but has become increasingly difficult to define. It shares, to some extent, common meanings in both biological and psychological sciences. Stress typically describes a negative concept that can have an impact on one.s mental and physical well-being, but it is unclear what exactly defines stress and whether or not stress is a cause, an effect, or the process connecting the two. An interrelationship between stress and periodontal disease has been suspected for centuries, but evidence to explain the connection has only elucidated in the past few decades. The purpose of this review article is to provide the progression of evidence present in the field of stress and periodontal disease for dental professionals so that they can better understand the link between stress and periodontal diseases. DOI: http://dx.doi.org/10.3126/hren.v10i2.6579 Health Renaissance 2012; Vol 10 (No.2); 126-131